PELATIHAN PAKEM MATEMATIKA SD DENGAN MENGGUNAKAN KOTAK KPK DAN FPB BAGI GURU SD DI KECAMATAN PONDOK KELAPA - Nurul Astuty Yensy (DHARMA RAFLESIA, 2018)
This activity aims to provide knowledge to teacher of elementary school about learning of mathematic PAKEM by using tool kit of KPK and FPB box in district of Pondok Kelapa and the manufacture technique, to motivate the teacher in order to create an innovative and creative mathematic learning media for the students. The training used the various methods such as workshop, demonstration, question and answer, discussion, guiding duties, monitoring and evaluation. The audiences in this activity were the teachers of SD N 10 Pondok Kelapa and SD N 2 Pondok Kelapa Central Bengkulu. Before the activity, the teacher knowledge about mathematic PAKEM was relatively less that only 9,1% know it, After the activity the ability and skill of the teacher in making the teaching toolbox of  KPK and FPB is good (83%), They produced this props with good results and can be applied to mathematic subject. The teacher's motivation to participate in this training is good (positive responses of participants in questionnaire by 95%). Keywords: learning of mathematic PAKEM, KPK and FPB box, elementary school.